Joint optimal decisions on pricing and warranty policy of duopoly supply chain with one common retailer - Kundu, Soumita; Chakrabarti, Tripti (Yugoslav Journal of Operations Research; Vol 30 No 2 (2020), 2020)
Early researches related to the interaction between manufactures for complimentary products, mainly considered price as the only dimension of competition. With the increasing competition in capturing the market share, manufactures can't compete by only lowering their prices. In this paper, we assume that besides the price, manufacturers choose warranty as a competitive strategy of two different but substitutable products in a duopoly supply chain with one common retailer. We propose two models (i) when only one manufacturer adopts warranty policy as a competitive strategy against the other (ii) when both manufacturers offer a warranty on their products. The models are analyzed by considering manufacturers' cooperative and non-cooperative strategies. The optimal pricing and warranty period decisions for both the models are discussed analytically as well as numerically.